Desde la interconexión hacia la integración eléctrica regional en la comunidad andina de naciones: camino recorrido y retos - Rojas Idrovo, Miriam (2020)
The regional electrical interconnection has diverse expressions in Latin America that have been configured within the framework of the evolution of integration ideas that range from the old regionalism, open regionalism and post-neoliberal or post-hegemonic regionalism. The main goal is to develop a true electrical integration in the Andean Community of Nations (CAN). For this purpose, the barriers that have prevented transit from interconnection to electrical integration have been reviewed; finding that the main obstacle is political and refers to the permanent tension that exists between sovereignty and cooperation agreed between member countries. In addition, regional integration must be achieved in three areas the politician who requires a consensus for the implementation of long-term stable regional policies that are not vulnerable to the political turns that are present in the region, for example achieve a cleaner and renewable energy matrix; a social integration where a true cohesion is achieved among the Andean citizens that goes beyond the traditional concept of independent and fractional republics; and an economic integration that demands the existence of national competitive markets, which lead to the regional market that includes Chile. This would force future appropriate discussions for the CAN, where the ideal should be a balance between state participation, through appropriate service regulation, and the participation of national and foreign investment, under conditions that guarantee access and quality to all citizens of the Andean community.